Hukum Tentang Perkawinan (Perbandingan Antara Kuh Perdata Indonesia, Inggris Dan Amerika) - Rizki Nurdiansyah; Muhammad Adam Damiri; Melly Rifa’atul Lailiyah (Universitas Sains dan Teknologi Komputer, 2023)
Laws regarding marriage are an important part of the legal system in various countries. In this context, this research aims to compare the laws regarding marriage in the Indonesian, British and American Civil Codes. The aim of this research is to analyze the differences and similarities in the legal regulation of marriage, including marriage requirements, the marriage process, and the rights and obligations of husband and wife in the three legal systems. This research uses a comparative legal approach, by analyzing legal regulations, court decisions, and relevant legal literature from the three countries. The data sources used include legal regulations regarding marriage, related court decisions, as well as legal literature that reviews aspects of marriage law in Indonesia, England and America. Data analysis was carried out by comparing the differences and similarities in marriage requirements, the marriage process, and the rights and obligations of married couples in the three countries. Factors such as religion, culture, and legal history will be considered in this comparative analysis. The results of this study show significant differences in the legal arrangements for marriage between the three countries. For example, in the Indonesian Civil Code, marriage can be religious or civil, while in England and America, civil marriage is the only legally recognized form. Marriage requirements such as minimum age, parental consent, and conditions for same-sex marriage may also differ in the three countries.